Study on the occurrence law and green control of grape gray mold from the perspective of ecological balance. Issue 1 (1st January 2021) - Shen, Fengying; Wu, Weigang; Han, Xing; Wang, Jiao; Li, Yaning; Liu, Daqun
ABSTRACT: With the increase of grape planting years, the base number of pathogenic seedlings and insect population is gradually rising. In addition, the introduction, breeding system and control of seedlings are not standardized and other human factors, the occurrence of Botrytis cinerea ( B.cinerea ) on grape is becoming more and more serious, resulting in a prominent problem of yield decline. In this paper, the occurrence of B.cinerea was monitored and its control effect was tested from the perspective of ecological balance. Finally, the biological characteristics and control of B.cinerea were studied. The spore catcher was used to catch the pathogen spores of B. cinerea, and the amount of sporangium scattering reached its peak from August to September Spore scattering is affected by meteorological factors, and the temperature has reached a very significant level, and the low temperature and high humidity conditions are conducive to the disease; The results showed that the resistance frequency of 304 B . cinerea strains to carbendazim, boscalid, pyrimethanil was higher than 50%; the volatile compounds produced by yeast ( Trichosproom sp.) YE-3-2 significantly inhibited the growth of B.cinerea (inhibition rate was 62.93%, according to the occurrence regularity of B.cinerea, the accurate and effective agricultural measures had a good control effect on B.cinerea, which could improve the quality of grape fruit and provide some help for the prevention of grape gray mold. GRAPHICAL ABSTRACT: uf0001